Operando Characterization Techniques for All‐Solid‐State Lithium‐Ion Batteries. Issue 6 (27th March 2021) - Strauss, Florian; Kitsche, David; Ma, Yuan; Teo, Jun Hao; Goonetilleke, Damian; Janek, Jürgen; Bianchini, Matteo; Brezesinski, Torsten
Abstract : Lithium‐ion batteries (LIBs), which utilize a liquid electrolyte, have established prominence among energy storage devices by offering unparalleled energy and power densities coupled with reliable electrochemical behavior. The development of solid‐state batteries (SSBs), utilizing a solid electrolyte layer for ionic conduction between the electrodes, could potentially offer further performance improvements in key areas such as energy density and safety. However, to date, SSBs remain unable to match the performance of their liquid counterparts. In light of renewed interest in accelerating the development of alternative energy storage devices, herein, a current overview of operando characterization techniques applied to solid‐state cells and related experimental setups is presented. Operando techniques, which allow materials to be studied as part of a dynamic system, have significantly advanced understanding of LIBs, and they offer the same potential for SSBs. To address this, a selection of analytical tools for probing interfacial/bulk electrochemical processes is highlighted and their advantages and challenges for studying various aspects of SSB chemistry are described. Finally, a perspective on how different techniques could support the future development of advanced SSBs is provided. Abstract : Operando techniques have significantly advanced understanding of conventional lithium‐ion batteries and they offer the same potential for solid‐state batteries (SSBs). Herein, an overview of operando characterization techniques applied to (inorganic) SSB cells is given and their challenges and possible future prospects are critically discussed.